SOSIALISASI BAHAYA PERGAULAN BEBAS DAN PENYALAHGUNAAN NARKOBA DI SMA NEGERI 1 BUNOBOGU - Rabia S. Manto; Sindi Hardiani Bain; Mohammad Safari; Moh. Rudini; Bahtiar Tamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Bunobogu Village is located in Buol Regency and represents a transitional area from rural to urban settings. This transformation is influenced by improved internet access and the introduction of external lifestyles and cultures brought by community members returning from migration. These changes make Bunobogu Village vulnerable to negative cultural influences, particularly drug abuse and promiscuous behavior. The majority of the population consists of young people, especially adolescents and young adults, who are the most vulnerable group to drug abuse and free association. Furthermore, most residents have a lower–middle economic status, which increases the risk of adolescents engaging in drug abuse and promiscuity as a means of coping with economic and social pressures. As a preventive effort, students participating in the Community Service Program (KKN) of Madako University conducted community service activities focused on the education sector, specifically at SMA Negeri 1 Bunobogu. The program was centered on socialization regarding drug abuse and the dangers of promiscuous behavior using an educational approach through material presentations, interactive discussions, and question-and-answer sessions. The results of this community service activity indicate an improvement in students’ understanding and awareness of the negative impacts of drug abuse and promiscuous behavior, as well as the importance of maintaining healthy and ethical conduct. This program is expected to serve as an initial step in fostering a knowledgeable, responsible, and resilient young generation capable of facing social challenges in the modern era.